Development of "Smart Character Expression" (PRESTER) Application Prototype to Enhance Emotional Intelligence in Deaf Adolescents - Fica Asniarno; Ravik Karsidi; Joko Yuwono (PAEDAGOGIA, 2026)
Deaf adolescents often face significant barriers in understanding facial expressions and emotions during social interactions due to limited access to auditory information. This research aims to develop a prototype of the "Smart Character Expression" (PRESTER) application as an adaptive learning medium to improve the emotional intelligence of deaf adolescents. Utilizing the Research and Development (R&D) method with the ADDIE model, this study integrates Universal Design for Learning (UDL) principles to ensure content accessibility. The result was an Android-based application featuring a sign language dictionary, various expression forms, and a sign gesture-scanning feature that visually translates emotional meanings. Validation from material and media experts indicates that the prototype is highly feasible. The prototype demonstrates strong potential in bridging the emotional recognition gap for deaf users.